Purple is the new pink: feminism as a commodity and as a marketing strategy in advertisements - Franco, Yanna G.; Bordón Ojeda, Marisa; García-Alonso, Claudia (Investigaciones Feministas (Feminist Research), 2022)
Introduction: This paper suggests that purple, a symbol of the feminist struggle, is been used as an advertising tool and as a consumer label to address the female target, subverting its political meaning, making invisible the real causes of inequality, and contributing to the commodification of feminism. Methods: A sample of six ads of food, beauty, personal hygiene and fashion products using purple as an advertising claim was selected to explore to what extent they fullfills the five criteria established by Becker-Herby (2016) to determine that a given campaign can be considered feminist advertising or "femvertising"; afterwards, we assessed whether these ads create a social imaginary around the color purple that collaborates to break with the gender binarism stereotypes or, on the contrary, to perpetuate them, simply by replacing pink with purple. Results: It is apparent that advertising has created a market niche for purple in which "feminism" and femininity coexist and which disguises economic interests under the guise of messages that advocate equality. Conclusions and contribution: It is true that “femvertising” strategies launch more positive messages than traditional advertising regarding what is considered feminine beauty or the role of women in society. However, these messages are individualistic in nature, aimed simply at reaching today’s women, who are unlikely to identify themselves with overtly sexist messages; they deprive not only the color purple of political content but also the very concept of female empowerment and, in short, they use the feminist agenda to different degrees in serving objectives that are very different from those pursued by feminism.